Metabolic profiling and pharmacological evaluation of alkaloids in three Murraya species - Huang, Huaxi; Geng, Xiaoshan; Wang, Lili; Wang, Xuexue; Liu, Fanglin; Peng, Yude; Tang, Chunfeng; Chen, Rong; Liu, Qin (Frontiers in Plant Science, 2025)
This study comprehensively investigated the metabolic profiling, pharmacological potential, and biosynthetic regulation of alkaloids in three Murraya species (M. exotica, M. kwangsiensis, and M. tetramera). Through integrative multi-omics approaches, including metabolomics, transcriptomics, network pharmacology, and molecular docking, a total of 77 alkaloids were identified, categorized into 18 structural classes. Comparative analysis revealed species-specific accumulation patterns, with 50 alkaloids shared among all three species and unique metabolites detected in M. exotica and M. kwangsiensis. Principal component analysis (PCA) confirmed distinct alkaloid profiles, highlighting interspecies divergence. Network pharmacology identified 427 potential targets for 12 bioactive alkaloids, with core targets (PIK3CA, PIK3CD, MAPK8, and JAK2) implicated in cancer-related pathways such as PI3K-Akt signaling. Molecular docking demonstrated strong binding affinities between key alkaloids (tombozine, aegeline, and crotaleschenine) and oncogenic targets, suggesting antitumor mechanisms via modulation of proliferation and apoptosis. Transcriptomic analysis elucidated the biosynthetic pathway of tombozine, linking differential gene expression (DDC/TDC homologs) to species-specific alkaloid accumulation. These findings underscore the pharmacological diversity of Murraya alkaloids and provide a foundation for targeted drug development and sustainable utilization of medicinal plant resources.